Synthesis and Biopharmaceutical Evaluation of Imatinib Analogues Featuring Unusual Structural Motifs. Issue 1 (20th November 2015) - Nicolaou, Kyriacos C.; Vourloumis, Dionisios; Totokotsopoulos, Sotirios; Papakyriakou, Athanasios; Karsunky, Holger; Fernando, Hanan; Gavrilyuk, Julia; Webb, Damien; Stepan, Antonia F.
Abstract: A convenient synthesis of imatinib, a potent inhibitor of ABL1 kinase and widely prescribed drug for the treatment of a variety of leukemias, was devised and applied to the construction of a series of novel imatinib analogues featuring a number of non‐aromatic structural motifs in place of the parent molecule's phenyl moiety. These analogues were subsequently evaluated for their biopharmaceutical properties (e.g., ABL1 kinase inhibitory activity, cytotoxicity). The bicyclo[1.1.1]pentane‐ and cubane‐containing analogues were found to possess higher themodynamic solubility, whereas cubane‐ and cyclohexyl‐containing analogues exhibited the highest inhibitory activity against ABL1 kinase and the most potent cytotoxicity values against cancer cell lines K562 and SUP‐B15. Molecular modeling was employed to rationalize the weak activity of the compounds against ABL1 kinase, and it is likely that the observed cytotoxicity of these agents arises through off‐target effects. Abstract : Revelations : The design, convenient synthesis and evaluation of imatinib, a potent anticancer agent that inhibits ABL1 kinase, and analogues provide valuable insights into biopharmaceutical properties imparted by novel structural motifs, such as bicyclo[1.1.1]pentane and cubane.